Transgenic Rabbit Models in Proarrhythmia Research - Baczkó, István; Hornyik, Tibor; Brunner, Michael; Koren, Gideon; Odening, Katja E. (Frontiers in Pharmacology, 2020)
Drug-induced proarrhythmia constitutes a potentially lethal side effect of various drugs. Most often, this proarrhythmia is mechanistically linked to the drug's potential to interact with repolarizing cardiac ion channels causing a prolongation of the QT interval in the ECG. Despite sophisticated screening approaches during drug development, reliable prediction of proarrhythmia remains very challenging. Although drug-induced long-QT-related proarrhythmia is often favored by conditions or diseases that impair the individual's repolarization reserve, most cellular, tissue and whole animal model systems used for drug safety screening are based on normal, healthy models. In recent years, several transgenic rabbit models for different types of long QT syndromes (LQTS) with differences in the extent of impairment in repolarization reserve have been generated. These might be useful for screening / prediction of a drug's potential for long-QT-related proarrhythmia, particularly as different repolarizing cardiac ion channels are impaired in the different models. In this review, we summarize the electrophysiological characteristics of the available transgenic LQTS rabbit models, and the pharmacological proof-of-principle studies that have been performed with these models - highlighting the advantages and disadvantages of LQTS models for proarrhythmia research. In the end, we give an outlook on potential future directions and novel models.